Textbook of Biochemistry for Medical Students - Vasudevan, DM; S, Sreekumari; Vaidyanathan, Kannan (New Delhi : Jaypee, 2016)
Fully revised, new edition presenting students with latest advances in field of biochemistry. Features clinical case studies, MCQs, short questions, essays and viva voce questions for revision.
Keywords: Biochemistry; Biochemistry, MCQs and Self -- assessment